The importance of public management in the local mayor of Bosa, in the City of Bogotá (2020)
Public management is based on accountability, on its effectiveness and efficiency, in which it is measured by results, the Colombian Political Constitution allows to exercise vigilance over the management of the people in charge; In this case, the public management of the town of Bosa for the period 2017 - 2020 will be analyzed, in which it seeks to strengthen economic, social and environmental development and public works, to achieve its central objective it establishes it with pillars and transversal axes, such as equality , social inclusion, increase and improve space and public infrastructure, as well as security; When monitoring the work in these years of history, it is identified that on some occasions, it could not meet its objectives to 100%, it is important to clarify that due to administrative changes and because of the COVID-19 pandemic, it could interfere in the fulfillment of the year 2020, and focused on protecting the lives of the population, with humanitarian aid